The role of Nrf2-Keap1 axis in colorectal cancer, progression, and chemoresistance - Mohammad Reza Sadeghi; Farhad Jeddi; Narges Soozangar; Mohammad Hossein Somi; Nasser Samadi (Tumor Biology)
Colorectal cancer is the third common cancer after lung and genital cancers worldwide with more than 1.2 million new cases diagnosed annually. Although extensive progress has been made in the treatment of colorectal cancer, finding novel targets for early diagnosis and effective treatment of these patients is an urgent need. Nuclear factor-erythroid 2–kelch-like ECH-associated protein 1 signaling pathway plays a key role in protecting cells from the damage of intracellular oxidative stress and extracellular oxidizing agents. Nuclear factor-erythroid 2 is a transcription factor that creates intracellular redox homeostasis via transcriptional activity and interaction with kelch-like ECH-associated protein 1. Furthermore, it contributes to survival and chemoresistance of colorectal cancer cells which is mediated by overexpression of cytoprotective and multidrug resistance genes. In this review, the dual role of nuclear factor-erythroid 2 signaling in induction of colorectal cancer cell survival and death as well as the possibility of targeting nuclear factor-erythroid 2–kelch-like ECH-associated protein 1 axis as an advanced strategy in prevention and effective treatment of colorectal cancer patients have been discussed.